Cutting-edge bioorthogonal chemistry: Innovations, practical applications, and emerging trends - Chetry, Anup Basnet (European Journal of Chemistry, 2024)
Bioorthogonal chemistry has emerged as a pivotal field in molecular science, offering transformative tools for applications in drug discovery, imaging, and molecular biology. This review provides a comprehensive analysis of recent advancements in bioorthogonal chemistry, emphasizing key innovations, practical applications, and future research directions. We explore state-of-the-art bioorthogonal reactions, including Staudinger ligation, strain-promoted azide-alkyne cycloaddition (SPAAC), and tetrazine ligation, detailing their mechanisms, advantages, and limitations. The review highlights significant innovations such as novel fluorogenic probes, improved catalysts, and enhanced reaction conditions that have expanded the utility and efficiency of these reactions. Practical applications are examined, showing how these advances have revolutionized fields like live-cell imaging, targeted drug delivery, and molecular labeling. Looking to the future, we discuss emerging trends and potential research avenues, including the integration of bioorthogonal chemistry with other advanced technologies and the development of new reaction methodologies. This review provides a detailed overview of the current state of bioorthogonal chemistry and outlines its future potential, serving as a valuable resource for researchers and practitioners in the field.